2019
DOI: 10.15557/jou.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the left subclavian artery in an infant with tetralogy of Fallot, right aortic arch and DiGeorge syndrome. Echocardiographic diagnostic case study

Abstract: We present a case of a 6-month-old infant with an isolated left subclavian artery coexistent with right-sided aortic arch, tetralogy of Fallot and DiGeorge syndrome, with an emphasis on echocardiographic detection of this extremely rare anomaly. Specific difficulties related to echocardiographic visualization of abnormally coursing artery were a result of significantly limited ultrasonographic access due to the absence of thymus and a very close proximity of the left subclavian artery and left common carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, only two studies have reported each reported one ISA patient with a chromosome 22q11 deletion. 15,16 Both patients presented with a left-sided ISA in a right-sided aortic arch; one patient had a tetralogy of Fallot, while the other had no intracardiac defects. Our findings demonstrate that an ISA can occur in a normal or mirrorimage aortic arch with a 22q11 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have reported each reported one ISA patient with a chromosome 22q11 deletion. 15,16 Both patients presented with a left-sided ISA in a right-sided aortic arch; one patient had a tetralogy of Fallot, while the other had no intracardiac defects. Our findings demonstrate that an ISA can occur in a normal or mirrorimage aortic arch with a 22q11 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Amongst cyanotic heart diseases, it is seen more frequently in TOF with a right aortic arch. [4][5][6] The embryological origin of an isolated subclavian artery as put forth by Edward 1948, 1 is explained by the involution of tissue between the left carotid and left subclavian artery and regression of dorsal aortic root tissue distal to the left ductus. Persistence of the right ductus arteriosus may sometimes result in a dual patent ductus arteriosus (PDA) in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical implications of an isolated subclavian artery with a patent ductus arteriosus in a TOF indicate a natural palliation in the form of a systemic to pulmonary shunt as seen in our case. 5,6 But with a decreased pulmonary blood flow situation, these children may present with episodes of vertebrobasilar insufficiency with a pulmonary run off or even stunted growth of the affected arm 7 in the long run. Fortunately, we did not encounter any of these features in our patient.…”
Section: Discussionmentioning
confidence: 99%